Acute physiological response to aerobic short-interval training in trained runners - Wallner, D.; Simi, H.; Tschakert, G.; Hofmann, P. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To analyze the acute physiological response to aerobic short-interval training (AESIT) at various high-intensity running speeds. A minor anaerobic glycolytic energy supply was aimed to mimic the characteristics of slow continuous runs. Methods: Eight trained male runners (maximal oxygen uptake [VO2max] 55.5 ± 3.3 mL/kg· min) performed an incremental treadmill exercise test (increments: 0.75 km/h· min). Two lactate turn points (LTP1, LTP2) were determined. Subsequently, 3 randomly assigned AESIT sessions with high-intensity running-speed intervals were performed at speeds close to the speed (v) at VO2max (vVO2max) to create mean intensities of 50%, 55%, and 60% of vLTP1. AESIT sessions lasted 30 min and consisted of 10-s work phases, alternated by 20-s passive recovery phases. Results: To produce mean velocities of 50%, 55%, and 60% of vLTP1, running speeds were calculated as 18.6 ± 0.7 km/h (93.4% vVO2max), 20.2 ± 0.6 km/h (101.9% vVO2max), and 22.3 ± 0.7 km/h (111.0% vVO2max), which gave a mean blood lactate concentration (La) of 1.09 ± 0.31 mmol/L, 1.57 ± 0.52 mmol/L, and 2.09 ± 0.99 mmol/L, respectively. La at 50% of vLTP1 was not significantly different from La at vLTP1 (P = .8894). Mean VO2 was found at 54.0%, 58.5%, and 64.0% of VO2max, while at the end of the sessions VO2 rose to 71.1%, 80.4%, and 85.6% of VO2max, respectively. Conclusion: The results showed that AESIT with 10-s work phases alternating with 20 s of passive rest and a running speed close to vVO2max gave a systemic aerobic metabolic profile similar to slow continuous runs.